A case for a shari’ah compliant alternate credit system to facilitate working capital management for micro, small and medium enterprises in Malaysia - Raheem, Mohamed Mahees; Mydin Meera, Ahamed Kameel (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM), 2018)
Studies and statistics have shown that micro, small and medium enterprises (MSMEs) enhance competition through economy-wide entrepreneurship, encouraging innovation and improving efficiency as their industries grow. In an increasingly globalized marketplace, it is important for Malaysian MSMEs to remain competitive in order to survive. Due to their size, they face many problems with regards to business operations. One of the main problems is access to financing for working capital management. This paper seeks to identify the main problems faced by Malaysian MSMEs in raising finance to meet their working capital requirements in their business operations, and also delve into the concept of trade credit and its employment in MSME business practices. Finally, the elements of an alternative strategy of working capital management will be proposed and discussed for the betterment of the MSMEs in Malaysia.